Comparative Financial Performance and Stock Valuation of Bottled Water Company Listed on the Indonesia Stock Exchange (CLEO and ADES) - Restu Amalia; Ana Noveria (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The bottled water industry in Indonesia demonstrates strong growth potential driven by population growth, urbanization, and increasing consumer awareness of health and water quality. This study compares the financial performance and stock valuation of two bottled water companies listed on the Indonesia Stock Exchange, PT Sariguna Primatirta Tbk (CLEO) and PT Akasha Wira International Tbk (ADES). A quantitative descriptive approach was employed using secondary data from annual reports and financial statements covering 2017–2025. Financial performance was evaluated through profitability, liquidity, activity, and solvency ratios, while stock valuation was assessed using Growth at a Reasonable Price (GARP), Relative Valuation and Discounted Cash Flow (DCF) methods. The results indicate that ADES outperformed CLEO in profitability, liquidity, and return on invested capital, supported by its diversified business portfolio. In contrast, CLEO demonstrated stronger operational efficiency through higher asset turnover and a shorter cash conversion cycle. Valuation analysis revealed that ADES was undervalued, with intrinsic values ranging from Rp26,883 to Rp49,028 and a margin of safety between 37% and 65%. Conversely, CLEO appeared overvalued, with intrinsic values ranging from Rp260 to Rp393 and margin of safety between -29% and -53%. These findings suggest that ADES is more attractive for value-oriented investors, while CLEO remains appealing for growth-oriented investors.